Національно-патріотичне виховання в системі забезпечення державної безпеки - Денисенко, Валентин Валентинович; Denysenko, Valentyn Valentynovich (Київський інститут Національної гвардії України, 2026)
Магістерська робота присвячена дослідженню системи національно-патріотичного виховання як ключового чинника забезпечення державної безпеки України. У роботі розкрито історичні та методологічні основи формування української національної ідеї, проаналізовано еволюцію поглядів на патріотичне виховання, його роль у зміцненні державності та духовної єдності народу. Здійснено аналіз нормативно-правової бази, яка визначає засади реалізації національно-патріотичної політики в сучасній Україні. У дослідженні розглянуто систему суб’єктів і об’єктів патріотичного виховання (сім’я, заклади освіти, держава, громадські організації, медіа), їхню взаємодію та вплив на формування громадянської ідентичності особистості. Проаналізовано сучасні форми та методи патріотичного виховання, що поєднують традиційні та інноваційні підходи: освітні програми, волонтерські ініціативи, культурно-просвітницькі проекти, використання інформаційно-комунікаційних технологій. Окрему увагу приділено визначенню пріоритетних напрямів розвитку національно-патріотичного виховання в умовах воєнних загроз, інформаційних впливів і деструктивних пропагандистських кампаній. У роботі розроблено рекомендації щодо вдосконалення змісту, форм і методів виховання на рівні державної політики, освітніх інституцій та громадянського суспільства. Розкрито роль інформаційно-комунікаційних технологій у формуванні цифрового патріотизму, підвищенні інформаційної грамотності молоді та протидії дезінформації. Зроблено прогноз щодо впливу ефективної системи національно-патріотичного виховання на зміцнення національної безпеки, єдності українського суспільства й утвердження духовно-моральних цінностей народу. Результати дослідження мають практичне значення для розробки державних програм патріотичного виховання, удосконалення навчально-виховної роботи у закладах освіти та підготовки фахівців у сфері державної безпеки.
National and patriotic education in the system of state security provision of Ukraine
The master’s thesis is devoted to the study of the system of national and patriotic education as a key factor in ensuring the state security of Ukraine. The work reveals the historical and methodological foundations of the formation of the Ukrainian national idea, analyzes the evolution of views on patriotic education, and highlights its role in strengthening statehood and the spiritual unity of the nation. The research includes an analysis of the legal framework regulating the implementation of national-patriotic policy in modern Ukraine. The study examines the system of subjects and objects of patriotic education (family, educational institutions, the state, public organizations, media), their interaction, and their influence on the formation of an individual’s civic identity. Modern forms and methods of patriotic education are analyzed, combining traditional and innovative approaches such as educational programs, volunteer initiatives, cultural and educational projects, and the use of information and communication technologies. Particular attention is paid to identifying priority areas for the development of national and patriotic education in the context of military threats, information influence, and destructive propaganda campaigns. The thesis provides recommendations for improving the content, forms, and methods of patriotic education at the levels of state policy, educational institutions, and civil society. The role of information and communication technologies in shaping digital patriotism, increasing media literacy among youth, and countering disinformation is revealed. The author provides a forecast of how an effective system of national and patriotic education contributes to strengthening national security, social unity, and the establishment of the spiritual and moral values of the Ukrainian people. The results of the research have practical significance for developing state programs of patriotic education, improving educational and training activities in educational institutions, and preparing specialists in the field of state security
Keywords: національно-патріотичне виховання; national and patriotic education; державна безпека; громадянська ідентичність; інформаційна стійкість; духовні цінності; цифровий патріотизм; система освіти; воєнні загрози; state security; civic identity; information resilience; spiritual values; digital patriotism; education system; military threats